Technohumanistic Education: Building Harmony between Technology and Humanity in 21st Century Learning - Anggreni, Ni Luh Putu Yesy; Wesnawa, I Gede Astra; Astawa, Ida Bagus Made; Sendratari, Luh Putu (Indian Journal of Information Sources and Services, 2025)
Technohumanistic teaching aims to balance technical progress with human values in learning. However, the speedy shifts in 21st century technology do not always strengthen human character in education. Alternatively, technohumanistic pedagogy combines principles focusing on humanity with digital aspects to craft a more significant, learner-focused, and principled educational experience. This research examines the notion of technohumanistic education, its value regarding the fourth industrial revolution and Society 5.0, plus its implications for curriculum development, study techniques, and educators’ roles through a qualitative approach and literature review. To obtain a generation with not only intelligence but also sympathy, adaptability and morality, it emphasizes the importance of balancing the use of technology and developing human characteristics by analyzing published works and considering wisely.